Enhancing contraceptive usage by immediate postpartum intra uterine contraceptive device insertion with evaluation of safety, acceptability and expulsion - Tirupati, Lekhya; Shivaraju, Pradeep; Lingegowda, Krishna; Srinivasan, Sabitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: India’s population which crossed one billion in 2000 is projected to reach 1.53 billion by 2050 making India the most populous country in world. In India 65% of women have unmet need for family planning in the first post-partum year. PPIUCD is highly effective, safe, long-acting, coitus independent and rapidly reversible method of contraception with very few side effects. Since there is tenfold increase in institutional deliveries due to maternity benefit schemes, postpartum period is potentially an ideal time to begin contraception as women are more strongly motivated and these women would leave the hospital with contraceptive in place. Methods: The present study was a prospective study to assess the acceptance rate of PPIUCD insertion and evaluation of safety of Cu T 380A when inserted within ten minutes of placental expulsion in 100 women delivering at PESIMSR, Kuppam. A specially designed proforma was used to collect the data of women attending hospital between period June 2016 to June 2017. Results: Out of 486 patients who were counselled only 100 women (20.57%) accepted for PPIUCD insertion. The acceptance rate of PPIUCD is 20.57%. Of 100 women who had PPIUCD insertion, 91 were seen at follow up, 76 (78.12%) women were continuing with no complaints and only 15 (16.4%) women developed complications. PPIUCD was found to be safe as there was no reported case of perforation or failure during usage. The complications like expulsion was found to be 1.09%, infection 5.4%, pain abdomen 5.4%, bleeding 1.09% and missing strings 5.4%. Conclusions: PPIUCD was demonstrably safe, having no reported case of uterine perforation. Expulsion rates are low implying more retention rates, thus more effective. Public awareness regarding the concept and advantages of PPIUCD insertion can be improved by mass media approach and creating strategies and training programmes under Government policies.